Book review: Knowledge and democracy as a source of legitimacy - Allan David Rodríguez Aristizábal; Juan Camilo Restrepo Restrepo (Revista CIDOB d'Afers Internacionals)
Review of the book: Peter, Fabienne. The grounds of political legitimacy. Oxford University Press, 2023, 232 págs.